Some aspects of biogeography with reference to zoning of the Far- Eastern Seas of Russia and adjacent waters of the Pacific Ocean - Oleg A. Ivanov; Vitaly V. Sukhanov (Известия ТИНРО, 2015)
Formation of biogeography, its methodological features, and its status as interdisciplinary science combining biological and geographical aspects are discussed. There is noted that the descriptive period of biogeography has passed, and now any «manifestation of life on the globe» requires its explanation. These explanations are reduced to three non-adversarial restrictions: environmental (ecology), temporal (history of origin, evolution), and spatial (geography). General regularities of life distribution over the Earth surface are analyzed, in particular the features of pelagic organisms habitat, and the concept of «dynamic biogeography» is discussed. Latitudinal zoning of epi- and mesopelagic layers in the Far-Eastern Seas of Russia and adjacent Pacific waters is proposed on the basis of data about areas and distribution of 493 species of nekton (fishes and squids) for the 30-year period (1980-2009) obtained from 27 thousand trawl samples caught in 272 expeditions. This zoning uses a new approach related to the chorological direction in marine biogeography realized with the index of latitudinal zoning (ILZ). For this index calculation, all types of species areas (formerly expressed in verbal forms) were identified with numerical codes, which were averaged for all species in each sample, then the regions with certain ILZ values and borders between them were determined on the maps of ILZ distribution, and latitudinal zones and subzones were defined. There is found that the epipelagic layer of the Okhotsk and Bering Seas corresponds to the high-boreal latitudinal subzone and the epipelagic layer of the northwestern Japan Sea and the major part of Russian EEZ in the Pacific corresponds to the low-boreal latitudinal subzone. Fauna of nekton in the mesopelagic layer of all studied regions corresponds by its chorological structure to the low-boreal latitudinal subzone. So, zoning of epipelagic and mezopelagic layers is significantly different, with the fragmentation reducing with depth, possibly due to weakening of climatic factors influence. The biogeographical zoning is not literally zonal but corresponds to structure of the environments (water masses, fronts, currents, gyres, eddies, etc.).